Identification of salinity-related genes in ENO2 mutant (eno2−) of Arabidopsis thaliana - Yong-hua ZHANG; Chao CHEN; Zi-han SHI; Hui-mei CHENG; Jie BING; Xiao-feng MA; Chao-xing ZHENG; Hong-jie LI; Gen-fa ZHANG (Journal of Integrative Agriculture)
Abiotic stress poses a great threat to plant growth and can lead to huge losses in yield. Gene enolase2 (ENO2) is important in resistance to abiotic stress in various organisms. ENO2 T-DNA insertion mutant (eno2−) plants of Arabidopsis thaliana showed complete susceptibility to sodium chloride treatment when were analyzed either as whole plants or by measuring root growth during NaCl treatment. Quantitative real-time RT-PCR (RT-qPCR) was performed to investigate the expression profile of ENO2 in response to NaCl stress in Arabidopsis. The transcript level of ENO2 was rapidly elevated in 300 mmol L−1 NaCl treatment. ENO2 also responded to 300 mmol L−1 NaCl treatment at the protein level. To illuminate the mechanism underlying ENO2 resistance to salt at the transcriptional level, we studied the wild-type and eno2− Arabidopsis lines that were treated with 300 mmol L−1 NaCl for 18 h using 454 GS FLX, which resulted in an expressed sequence tag (EST) dataset. A total of 961 up-regulated and 746 down-regulated differentially expressed genes (DEGs) were identified in the pairwise comparison WT-18 h:eno2−−18 h. The DEGs were identified and functionally annotated using the databases of Gene Ontology (GO) and the Kyoto encyclopedia of genes and genomes (KEGG). The identified unigenes were subjected to GO analysis to determine biological, molecular, and cellular functions. The biological process was enriched in a total of 20 GO terms, the cellular component was enriched in 13 GO terms, and the molecular function was enriched in 11 GO terms. Using KEGG mapping, DEGs with pathway annotations contributed to 115 pathways. The top 3 pathways based on a statistical analysis were biosynthesis of the secondary metabolites (KO01110), plant-pathogen interactions (KO04626), and plant hormone signal transduction (KO04075). Based on these results, ENO2 contributes to increased resistance to abiotic stress. In particular, ENO2 is involved in some of the metabolic stress response pathways in Arabidopsis. Our work also demonstrates that this EST dataset will be a powerful resource for further studies of ENO2, such as functional analyses, investigations of biological roles, and molecular breeding. Additionally, 3-phosphoglycerate kinase (PGK), 3-phosphoglycerate kinase 1 (PGK1), triosephosphate isomerase (TPI), and pyruvate kinase (PK) in glycolysis interactions with ENO2 were verified using the yeast two-hybrid experiment, and ENO2 may regulate the expression of PGK, PGK1, TPI, and PK. Taken together, the results from this study reflects that ENO2 gene has an important role in the response to the high salt stress.